Changes in Documentation of Social Risk Factor Diagnosis Codes: Comparison of Medicaid Accountable Care Organization Model Types - Kevin H Nguyen; Kenneth Lim; Kathryn Thompson; Sarah H Gordon; Collette N Ncube; Lois McCloskey; Megan B Cole (Health Affairs Scholar, 2026)
Abstract Introduction Identifying social risk factors during the perinatal period may improve pregnancy-related outcomes. In 2018, Massachusetts’ Medicaid program implemented an accountable care organization (ACO)—which required social risk factor screening–under two ACO model types: Model A (health system/Medicaid managed care plan partnership model) and Model B (primary care practice model). Methods Using 2016-2020 Massachusetts All Payer Claims Database and a difference-in-differences (DiD) design, we compared changes in any social risk factor documentation (i.e., ICD-10 Z-codes) for Medicaid-enrolled deliveries in non-ACOs vs ACO Model A vs Model B, measured separately for the prenatal period, 60-days postpartum, 12-months postpartum, and the perinatal period. Secondary outcomes included documentation of specific Z-codes related to homelessness and food insecurity. Results Both Models A (DiD=1.03 PP, p<0.001) and Model B (DiD=0.65 PP, p<0.001) were associated with significant increases in Z-code documentation of food insecurity in the perinatal period. Model B was associated with a significant increase in Z-code documentation of homelessness in the perinatal period (DiD=1.10 PP, p<0.001) but not Model A. Conclusions Massachusetts’ Medicaid ACO was associated with modest increases in Z-code documentation during the perinatal period, with some variation by ACO model type.